Analysis of 99Mo Production Capacity in Uranyl Nitrate Aqueous Homogeneous Reactor using ORIGEN and MCNP - A. Isnaeni; M.S. Aljohani; T.G. Aboalfaraj; S.I. Bhuiyan (Atom Indonesia, 2014)
99mTc is a very useful radioisotope in medical diagnostic procedure. 99mTc is produced from 99Mo decay. Currently, most of 99Mo is produced by irradiating 235U in the nuclear reactor. 99Mo mostly results from the fission reaction of  235U targets with a fission yield about 6.1%. A small additional amount is created from 98Mo neutron activation. Actually 99Mo is also created in the reactor fuel, but usually we do not extract it. The fuel will become spent fuel which is a highly radioactive waste. 99Mo production system in the aqueous homogeneous reactor offers a better method, because all of the 99Mo can be extracted from the fuel solution. Fresh reactor fuel solution consists of uranyl nitrate dissolved in water. There is no separation of target and fuel in an aqueous homogeneous reactor where target and fuel become one liquid solution, and there is no spent fuel generated from this reactor. Simulation of the extraction process is performed while reactor in operation (without reactor shutdown). With an extraction flow rate of 3.6 L/h, after 43 hours of reactor operation the production of 99Mo is relatively constant at about 98.6 curie/hour./hour.Received: 11 January 2014; Revised: 18 February 2014; Accepted: 28 February 2014